Invasive Aspergillosis Associated with a Foreign Body - Akifuddin Syed; Prashanth Panta; Imran Shahid; David H. Felix (Case Reports in Pathology)
Invasive aspergillosis is a serious complication in immunocompromised individuals. It is associated with a high mortality rate, which demands a combined approach involving radical surgery and antifungal therapy. Here, we describe a patient who presented with nonspecific fever, refractory to antimicrobial agents. Though it primarily involved the nasal cavity and sinuses, it perforated into the oral cavity causing palatal changes. Surprisingly, a foreign body was found in the involved tissues that might have acted as a nidus of infection. A sufficient dose (3 mg/kg/day) of liposomal amphotericin B was initiated soon after a thorough debridement procedure and the patient survived.